2009
DOI: 10.4012/dmj.28.396
|View full text |Cite
|
Sign up to set email alerts
|

The bone-healing effect of a xenograft in a rat calvarial defect model

Abstract: Bone grafts have been widely used to fill osseous defects in medicine, dentistry, and periodontology. The purpose of this study was to investigate the effects of a xenograft (Unilab Surgibone ® ) on experimentally created parietal bone defects in rats. To this end, 14 rats were employed in the present study and in each of them, 5-mm-diameter defects were created on the parietal bone. The right defect sites were filled with the xenograft material, while the left sites were used as control. After 30 days, the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 23 publications
1
32
0
2
Order By: Relevance
“…It was reported that Unilab Surgibone was tested in critical sized defects in rats for one month and the biomaterial was seen biocompatible and useful. 32 Moreover, in the case of the cytotoxic activities, the xenograft evaluated here showed no cytotoxicity for the cells. Therefore, it seems as a useful material.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Unilab Surgibone was tested in critical sized defects in rats for one month and the biomaterial was seen biocompatible and useful. 32 Moreover, in the case of the cytotoxic activities, the xenograft evaluated here showed no cytotoxicity for the cells. Therefore, it seems as a useful material.…”
Section: Discussionmentioning
confidence: 99%
“…As there is a well-documented model for the assessment of bone healing, experimental studies on the rat skull is the gold standard for testing tissue reaction to root canal filling material [3,13,14]. For each group, the control orifice was 1 of the 4 orifices made in the calvaria, which was free of any tested material.…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the ability of BMP-7 derived-peptide chitosan nanometer hydroxyapatite collagen composite to promote bone regeneration, we select the rat skull defect as experimental animal model, which is characterized by the advantages of simple, standard and reproducible. [11] Based on the results of the preliminary experiment, the researchers selected 1 mg as the amount of the composite polypeptide, and polypeptide chitosan nanometer hydroxyapatite biomimetic collagen composites and pure chitosan nanometer hydroxyapatite biomimetic collagen composites alone were respectively implanted into the rat skull defects. General observation, three dimensional reconstruction of CT and histological observation were performed at 6 and 12 weeks after the operation.…”
Section: Discussionmentioning
confidence: 99%